Membrane Assemblies with Soft Protective Layers: Dense and Gel‐Type Polybenzimidazole Membranes and Their Use in Vanadium Redox Flow Batteries. Issue 50 (1st November 2022) - Do, Xuan Huy; Abbas, Saleem; Ikhsan, Muhammad Mara; Choi, Seung‐Young; Ha, Heung Yong; Azizi, Kobra; Hjuler, Hans Aage; Henkensmeier, Dirk
Abstract: Polybenzimidazole (PBI) membranes show excellent chemical stability and low vanadium crossover in vanadium redox flow batteries (VRFBs), but their high resistance is challenging. This work introduces a concept, membrane assemblies of a highly selective 2 µm thin PBI membrane between two 60 µm thick highly conductive PBI gel membranes, which act as soft protective layers against external mechanical forces and astray carbon fibers from the electrode. The soft layers are produced by casting phosphoric acid solutions of commercial PBI powder into membranes and exchanging the absorbed acid into sulfuric acid. A conductivity of 565 mS cm −1 is achieved. A stability test indicates that gel mPBI and dense PBI‐OO have higher stability than dense mPBI and dense py‐PBI, and gel/PBI‐OO/gel is successfully tested for 1070 cycles (ca. 1000 h) at 100 mA cm −2 in the VRFB. The initial energy efficiency (EE) for the first 50 cycles is 90.5 ± 0.2%, and after a power outage stabilized at 86.3 ± 0.5% for the following 500 cycles. The initial EE is one of the highest published so far, and the materials cost for a membrane assembly is 12.35 U.S. dollars at a production volume of 5000 m 2, which makes these membranes very attractive for commercialization. Abstract : Polybenzimidazole (PBI) membranes efficiently hinder the crossover of vanadium ions, but have high resistance. Thin PBI membranes (e.g., <4 µm) have adequate resistance but need to be supported. Here, thin PBI is protected by assembling it between two 60 µm thick soft sulfuric acid swollen PBI gel layers, which are highly conductive (>500 mS cm −1 ) and promise low interfacial resistance.